An Online Non-Invasive Condition Monitoring Method for Stepping Motor CRDM in HTGR - S. Bakhri; N. Ertugrul (Atom Indonesia, 2016)
Control Rod Drive Mechanism (CRDM) based on stepping motor is one of the components applied in High Temperature Gas Coold Reactor (HTGR) to control the reactivity as well as to maintain the safety of reactor. The stepping motor requires a unique condition monitoring to avoid any failures especially due to the specific environments of CRDM in HTGR such as the allowable of high temperature, high radiation and the location of stepper motor inside a pressure shell. This research aims to demonstrate an online non-invasive condition monitoring method without direct access to the CRDM of HTGR based on voltage and stator current measurements. A simple stepping motor CRDM simulator is employed. The online condition monitoring is carried out by direct pattern matching of the output signals of logic generator block and the output signals of motor driver. The online method utilizes signature patterns of voltage and stator current signals of the healthy motor as a baseline for healthy motor. In addition, the method is applied to detect high-resistance problem on the connector between the motor driver block and the stepper motor to show the effectiveness and the applicability of this method. The online condition monitoring system demonstrates a capability to identify a minimum detectable simulated high-resistance for about 2.9% which decreases the measured stator current and motor’s torque for around 5.1% and 3.3%, respectively. The paper also points out signatures of healthy motor, including mutual inductions of the motor’s winding in voltage and current measurement which can be used as the fault symptom indicators for online monitoring purposes.Received: 19 November 2014; Revised: 13 April 2016; Accepted: 22 June 2016